Peran Resiliensi dalam Meningkatkan Kesejahteraan Subyektif pada IRT Penuh Waktu yang Mengalami Burnout - Liuciana Handoyo Kirana; Fransisca Iriana Roesmala Dewi; Riana Sahrani (Universitas Kristen Maranatha, 2024)
The well-being of Stay-at-home Mothers (SAHM) has a very important role for all family members, which includes emotional and physical well-being. The sample in this study were SAHM who experienced burnout and this had an impact on family well-being. Many highly educated women leave their jobs and decide to become SAHM. However, as time goes by, SAHM experience burnout due to the new routine. Burnout is caused by household work and childcare that is never completed in daily life, resulting in physical and psychological fatigue. Resilience is the ability to bounce back when dealing with stress. This research consists of two variables, resilience as the independent variable and subjective well-being for mother as the dependent variable. The two measuring tools are Subjective Well-being for Mother (SWBM) and Connor-Davidson Resilience Scale (CD-RISC). Correlational quantitative methods were used in this research. Questionnaires were distributed to 317 housewives who had previously worked for at least six months and still had school-aged children. Burnout can occur in any age of SAHM, education, and socioeconomic status. This research proves that resilience has a good impact on SAHM who experience burnout to regain their well-being.